Towards the Poetics of the Early Mandelštam. Ja v chorovod tenej: an Analysis - Boris Andreevič Uspenskij (Studi Slavistici, 2024)
Mandelstam’s poem is divided into two opposing parts, in terms of content and style; they are united by the same lyrical subject. These two parts correspond to two parallel narrative plans. In the beginning, the unreal, afterlife world (the world of shadows) is presented, and then the earthly, real world. The first part describes the lyrical subject’s transition from being to non-being; the second part speaks of the life he has left behind which at the same time continues for him. The analysis of the poem leads to the conclusion that the world of shadows is treated by the poet as an Elysium of names, i.e. poetic words. It is a special reality created by poetic language. This poem appears as an illustration of Mandelstam’s early theoretical work on poetic language.